Working Capital Activities of Multinational Companies at McDonald's Company - Kiki Farida Ferine; Artunov Nofal; Rico Nur Ilham (Lafadz Jaya Publisher, 2023)
Working capital management is a branch of financial management that manages the working capital of a company to achieve optimal value. The purpose of holding working capital management is to produce the welfare of shareholders through obtaining optimal profits. The aim is to meet the company's liquidity, liability and supply needs for consumers. McDonald's is a fast-food restaurant that is still needed by the people of Indonesia and abroad. PT Rekso Nasional Food or better known as McDonald's Indonesia is a publicly traded fast food company with branches in Jakarta, Indonesia. The company was founded on February 23, 1991. This company is the only McDonald's franchisee in Indonesia. The entry of McDonald's or other large companies into Indonesia can have a complex impact on local companies. It is important for local companies to continue to adapt and innovate in the face of competition from international companies such as McDonald's.